Effect of sugar reduction on flavour release and sensory perception in an orange juice soft drink model. (30th June 2019) - Tsitlakidou, Petroula; Van Loey, Ann; Methven, Lisa; Elmore, J. Stephen
Highlights: Orange juice models were flavoured with seven characteristic volatile compounds (VCs). Nine retronasal attributes were affected by sugar content. Orthonasal "overripe orange" and six VCs increased with increasing sugar content. Total VC release was highly correlated with perceived intensity of "overripe orange". Abstract: To examine the effect of sugar reduction on the sensory perception of sweetened beverages, an orange juice soft drink model flavoured with seven characteristic compounds (hexanal, decanal, linalool, ethyl butanoate, α-pinene, β-myrcene and ( Z )-3-hexen-1-ol) was developed. Five samples were prepared with relevant sugar contents (5.2, 8.2, 9.7, 11.2 and 14.2 °Brix). Using retronasal quantitative descriptive analysis (QDA), nine attributes were found to differ significantly ( p  < 0.05) with sugar content. When the samples were evaluated orthonasally, only the attribute "overripe orange" significantly decreased ( p  < 0.05) with reduction of sugar content. Headspace solid-phase microextraction with gas chromatography–mass spectrometry showed that as sugar concentration decreased, the headspace concentration of six of the volatile compounds decreased, whilst ethyl butanoate remained constant. Principal component analysis revealed that the total release of the flavour compounds was highly correlated with the perceived intensity of the orthonasal attribute "overripe orange".